PENGEMBANGAN BAHAN AJAR IPA DENGAN MEDIA AUDIO VISUAL PADA TEMA SELAMATKAN MAKHLUK HIDUP DI PENDIDIKAN DASAR - Asa Anfaida Maslina (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
Thematic learning with a system in textbooks with various kinds of lesson content makes teachers and students experience material misunderstandings. The purpose of this study is to develop science teaching materials with audio visual media on the theme of saving sentient beings that are simple, easy to understand, effective, efficient, and easy to use.The results of this study are as follows: 1) a preliminary study that contains about real conditions, resulting in the use of science teaching materials with textbooks and assessment books. 2) the results of the need assessment in the form of questionnaires that indicate the value of 3.75 or really need. 3) developing printed teaching materials with audio-visual media supplements. 4) the results of the validation test with these science teaching materials are tested based on: a) Assessment of the suitability of the material coverage with a score of 96.9 or including "very feasible" to be used; b) The assessment of media experts is assessed based on the relevance of the media by getting a score of 89.2 or including "very reasonable" to use; c) Evaluation by Technology Science experts is assessed based on compatibility with technology science media by getting a score of 85.6 or including "very feasible" to use. 5) test the effectiveness of science teaching materials with audio visual media on the theme of saving sentient beings with a t test value of 6,798. then with these results that science teaching materials with audio visual media are effectively used for learning activities.